Spatial immune landscapes of SARS-CoV-2 gastrointestinal infection: macrophages contribute to local tissue inflammation and gastrointestinal symptoms - Xian, Shi-Ping; Li, Zhan-Yu; Li, Wei; Yang, Peng-Fei; Huang, Shen-Hao; Liu, Ye; Tang, Lei; Lai, Jun; Zeng, Fa-Min; He, Jian-Zhong; Liu, Yang (Frontiers in Cell and Developmental Biology, 2024)
Background In some patients, persistent gastrointestinal symptoms like abdominal pain, nausea, and diarrhea occur as part of long COVID-19 syndrome following acute respiratory symptoms caused by SARS-CoV-2. However, the characteristics of immune cells in the gastrointestinal tract of COVID-19 patients and their association with these symptoms remain unclear. Methodology Data were collected from 95 COVID-19 patients. Among this cohort, 11 patients who exhibited gastrointestinal symptoms and underwent gastroscopy were selected. Using imaging mass cytometry, the gastrointestinal tissues of these patients were thoroughly analyzed to identify immune cell subgroups and investigate their spatial distribution. Results Significant acute inflammatory responses were found in the gastrointestinal tissues, particularly in the duodenum, of COVID-19 patients. These alterations included an increase in the levels of CD68+ macrophages and CD3+CD4+ T-cells, which was more pronounced in tissues with nucleocapsid protein (NP). The amount of CD68+ macrophages positively correlates with the number of CD3+CD4+ T-cells (R = 0.783, p < 0.001), additionally, spatial neighborhood analysis uncovered decreased interactions between CD68+ macrophages and multiple immune cells were noted in NP-positive tissues. Furthermore, weighted gene coexpression network analysis was employed to extract gene signatures related to clinical features and immune responses from the RNA-seq data derived from gastrointestinal tissues from COVID-19 patients, and we validated that the MEgreen module shown positive correlation with clinical parameter (i.e., Total bilirubin, ALT, AST) and macrophages (R = 0.84, p = 0.001), but negatively correlated with CD4+ T cells (R = −0.62, p = 0.004). By contrast, the MEblue module was inversely associated with macrophages and positively related with CD4+ T cells. Gene function enrichment analyses revealed that the MEgreen module is closely associated with biological processes such as immune response activation, signal transduction, and chemotaxis regulation, indicating its role in the gastrointestinal inflammatory response. Conclusion The findings of this study highlight the role of specific immune cell groups in the gastrointestinal inflammatory response in COVID-19 patients. Gene coexpression network analysis further emphasized the importance of the gene modules in gastrointestinal immune responses, providing potential molecular targets for the treatment of COVID-19-related gastrointestinal symptoms.